Peningkatan Kemampuan Mengenal Warna Melalui Pemanfaatan Tutup Botol Minuman Sebagai Media Pembelajaran Pada Anak RA Permata Hati Sidokumpul Guntur Demak - Noor, Fu'ad Arif; Istikomah (EDUCATE : Journal of Education and Culture, 2024)
This research aims to determine the implementation of recognizing colors through the use of drink bottle caps at RA Permata Hati Guntur Demak and to determine the implementation of using drink bottle caps in order to improve color recognition at RA Permata Hati Guntur Demak. Data collection techniques in this research are through observation and documentation techniques . This type of research is classroom action research with qualitative descriptive data analysis. The subjects used were students of RA Permata Hati Guntur Demak with a population of 10 children. Data sources come from educators and educational staff. The results of the research show that the ability to recognize colors can be increased by using drink bottle caps. The research results increased gradually. In addition to being able to recognize colors, this media also gives students interest in learning and can recognize concrete objects. There was an increase in the ability to recognize colors by using drink bottle caps in the pre-cycle of 3 students, with an average score of 45.6 and a percentage of 30%, in the first cycle there was an increase of 4 children with an average score of 55.55 and a percentage of 40%. cycle II increased by 5 children with an average score of 72 and a percentage of 50% and cycle III increased by 9 children with an average score of 87.5 and a percentage of 90%.